Molecular mechanisms of pain regulation in patients with osteoarthritis - E. V. Chetina; G. A. Markova; E. A. Taskina; E. P. Sharapova; N. G. Kashevarova; L. I. Alekseeva; V. V. Kolomatsky; M. A. Makarov; A. L. Logunov; S. A. Makarov; A. N. Kuzin (Научно-практическая ревматология, 2016)
Objective: to study the mechanisms determining the level of pain on the basis of an analysis of the expression profiles of the genes involved in joint destruction, inflammation, and metabolic regulation in the blood of patients with osteoarthritis (OA) with different expression levels of the Mammalian Target Of Rapamycin (mTOR) gene and at different disease stages.Material and methods. Peripheral blood samples from 47 outpatients with OA, from 21 late-stage OA patients admitted to hospital for endoprosthetic knee joint replacement, and from 27 healthy individuals who formed a control group (mean age, 60.0±7.1, 56.6±8.9, and 58.6±8.3 years, respectively), as well as articular cartilage samples obtained intraoperatively from 21 patients with OA and at autopsy from previously healthy people (mean age, 38.2±4.3 years) who had died from trauma, were examined. Clinical, radiographic, ultrasound, and densitometric examination was performed. Total RNA was isolated from blood and after reverse transcription it was used to estimate gene expression levels in real-time polymerase chain reaction.Results and discussion. In the low mTOR gene expression subgroup, the expression of all the study genes proved to be at the control level, except the matrix metalloproteinase 9 (MMP9) gene, the expression of which was significantly higher. In the patients with a high expression of the mTOR gene and in those with late-stage OA, the expression of all the study genes was much higher than in the control group. There was a positive correlation of the gene expression of the transforming growth factor β1 (TGF-β1) (r = 0.594; p = 0.005) and cathepsin K (r = 0.595; p = 0.003) in the blood and articular cartilage of patients with late-stage OA.Conclusion. The different levels of pain in OA patients with different expression levels of the mTOR gene may be associated with the expression ratio of the genes MMP9 and tissue inhibitor of metalloproteinases 1 (TIMP1), the excessive or insufficient activity of the mTOR gene, and the expression of the growth factors TGF-І1 and vascular endothelial growth factor, which are involved in the processes of tissue regeneration.